Basic Literacy In Numeracy: Analysis of Misconceptions In Third Grade Elementary School Place Value Material - Pambudi, Gigih; Nindiasari, Hepsi (Universitas PGRI Sumatera Barat, 2025)
Mathematics, a core subject in schools, is crucial for developing logical and systematic thinking skills. One fundamental concept is place value, which helps students understand the position and value of digits in numbers. Proper understanding of place value is essential for learning more complex mathematical concepts like addition, subtraction, decimal operations, and fractions. However, many students often experience misconceptions about this concept, such as misinterpreting the value of digits. These misconceptions can lead to errors in more complex number operations and reduce students' confidence in their mathematical abilities. This study uses a qualitative method with a descriptive approach to systematically describe specific objects. Data collection techniques include interviews, observations, and documentation. Based on observations and interviews, it was found that students who experienced careless errors were 13%, concept errors were 9%, and a combination of both types of errors was 9%. Additionally, 6% of students experienced an inability to think mathematically or other learning disorders. Effective educational interventions, such as implementing constructivist learning, can reduce the likelihood of misconceptions. In conclusion, place value is the foundation of learning mathematics, and misconceptions in this area can have significant negative impacts on students. Teachers need to conduct deeper analyses and prepare better strategies to address these misconceptions.